Meningkatkan Umkm Melalui Sumber Daya Manusia Di Era Digitalisasi Bisnis Di Desa Daliwangun - Yusuf, Mohamad Fahmi; Wiratama, Dadang; Ulfa, Maria Arista; Pambudi, Wahyu Tri (Pakis Journal Institute, 2024)
The era of business digitalisations has opened up great opportunities for micro, Small, and medium Enterprises (MSMEs) to develop more quickly, including in Daliwangun Village. This service aims to indentify strategies for improving MSMEs through developing the quality of human resource (HR) that are adaptive to digital technology. This community service activity will be held on August 12, 2024. This event involved MSME assisted residents in Daliwangun village, Glagah district, Lamongan Regency. The method used is lecture and in-depth question and answer. The research result show that digitalizations training, strengthening technological literacy, and assistance in using digital marketing platforms play an important role in increasing the competitiveness of MSMEs.